PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII.2 SMPN 3 BANGKINANG - Putri, Hadindri Putri; Yuanita, Putri Yuanita; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is to improve mathematics outcomes by applying the cooperative learning model in type Two Stay Two Stray. The research is classroom action research (PTK) which to cycle. The subjects of this research were the first grade students of SMPN 3 Bangkinang academic year 2014/2015. This action research was conducted in two cycles. Each cycle has four stages, these were planning, action, observation, and reflection. Each end of the cycle performed quiz. Data collected through observation sheet showed the ctivity of teachers and learners increasingly performing well after doing the action. Based on the observations of researchers during the learning process in the classroom VIII.2 SMPN 3 Bangkinang, most of the students were active in the learning process are implemented. Achievement attitude in its development more visible in working LKPD, as evidenced by an increase in the number of learners who achieve good and very good category. Same with the achievement of skills of students, the number of learners who are skilled and skilled enough to rise. The percentage of students who achieve the KKM knowledge base score and daily tests (second cycle) respectively is 46,15 %, and 76,92 %. Action is successful if the state after the action better. The results showed that cooperative learning model in type Two Stay Two Stray can improve the learning process and improve learning outcomes VIII.2 grade math students SMPN 3 Bangkinang. Keywords: Cooperative Learning Model In Type Two Stay Two Stray, Learning Outcomes, Classroom Action Research